Summary of schemes for the assistance of the unemployable blind (1930)
1930 1930 1930s 6 pages Handed in by Mr Henderson Schemes for the Assistance of the Unemployable Blind. Breconshire. Augmented to £1 a week. Not eligible - Persons in receipt of Poor Law Relief. Buckinghamshire. Augmented to 15/- a week. Cost borne by County Council to the extent of £100 per annum, remainder by voluntary association. Carmarthenshire. Augmented to 12/6 a week in Rural Districts. Augmented to 17/- a week in Urban Districts. Derbyshire. Augmented to £1 a week. Generally required to be resident in the County for at least 1 year. In calculating income (1) fixed value of 5/- a week is placed upon board-lodgings received by blind persons living with relatives; (2) where persons are in receipt of interest from a capital sum such sum is deemed to be converted into an annuity; (3) blind wives living with husbands who are employed are considered individually. Devonshire. Augmented to 15/- a week. Durham. Augmented to £1 a week. Not eligible - Blind married, women with sighted husbands. East Riding. Augmented to 15/- a week. Not eligible - Persons in receipt of Poor Law Relief. Glamorgan. (a) Augmented to 22/6 a week - persons 20 years of age and over. (b) Augmented to 17/6 a week - single persons under 20 yrs. of age residing at home with parents. (c) Augmented to 10/- a week - wives whose husbands are in employment or in receipt of unemployment benefit. Grants takes the place of Poor Law Relief. Value of income derived from ownership of a house in which applicant resides assessed at 5/- a week. If grantee is admitted to a voluntary Hospital grant of 5/- a week only allowed when there is no income from any other source. Financial circumstances reviewed every six months. (c) Any pension received under the O.A.P. Acts deducted. Kesteven. Augmented to 15/- a week - persons living alone. Allowances of from 5/- a week to £4 a year - persons living with relatives or friends. Value of free lodgings taken into consideration. Cost borne by County Council to the extent of £300 per annum rest by voluntary society. 292/841.4/1/40